LEGAL PROTECTION FOR OUTSOURCING WORKERS AT PT RESKA MULTI USAHA - Agus Liyanto M. Sigalinging; Isnaini; Rafiqi (SOSIOEDUKASI, 2026)
This study critically examines the legal protection of outsourced workers at PT Reska Multi Usaha (RMU), a subsidiary of a state-owned enterprise (BUMN) that relies on an outsourcing model to support its operations in the transportation sector. The outsourcing model, often used for business efficiency, inherently creates vulnerabilities for workers due to indirect employment relationships, uncertain contract status, and potential rights gaps. This study aims to answer three main research questions: (1) how is the legal protection for outsourced workers at PT Reska Multi Usaha described? (2) how is the balance between the rights and obligations of outsourced workers at PT Reska Multi Usaha?; and (3) how is the implementation of legal protection for outsourced workers at PT Reska Multi Usaha? This study uses an empirical juridical research method with a statutory and conceptual approach. The data collection instruments are observation, documentation studies, and interviews, while the data analysis is descriptive analysis. The results of this study indicate that while normatively, it complies with labor laws and regulations, particularly Law No. 11 of 2020 concerning Job Creation and Government Regulation No. 35 of 2021, substantively, legal protection is not yet fully optimal. This is evident in the persistence of uncertainty in employment relationships due to repeated contract extensions and the disparity in treatment between outsourced and permanent workers.